2018
DOI: 10.1016/j.joi.2018.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Which US and European Higher Education Institutions are visible in ResearchGate and what affects their RG score?

Abstract: While ResearchGate has become the most popular academic social networking site in terms of regular users, not all institutions have joined and the scores it assigns to academics and institutions are controversial. This paper assesses the presence in ResearchGate of higher education institutions in Europe and the US in 2017, and the extent to which institutional ResearchGate Scores reflect institutional academic impact. Most of the 2,258 European and 4,355 US higher educational institutions included in the samp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 43 publications
(44 reference statements)
1
23
0
Order By: Relevance
“…Our data suggest that assessing the number of citations per article or h-indexes for individuals and institutions using ResearcherID or ResearchGate gives overall results that are quite different from those obtained using the Scopus database. This confirms previous findings which have shown that the usefulness of bibliometric indicators derived from ASNs for institutions [41][42][43] or individuals [30,37,44] is not clear (results are controversial depending on the ASNs and parameters studied).…”
Section: Number Of Citations Per Article and H-indexsupporting
confidence: 91%
“…Our data suggest that assessing the number of citations per article or h-indexes for individuals and institutions using ResearcherID or ResearchGate gives overall results that are quite different from those obtained using the Scopus database. This confirms previous findings which have shown that the usefulness of bibliometric indicators derived from ASNs for institutions [41][42][43] or individuals [30,37,44] is not clear (results are controversial depending on the ASNs and parameters studied).…”
Section: Number Of Citations Per Article and H-indexsupporting
confidence: 91%
“…However, Ali et al (2017) compared the RG score of 350 Higher Education institutions in Pakistan to their positions within the 2015 ranking of Pakistani Higher Education institutions and Quacquarelli Symonds rankings, reporting no correlation. Both findings may be explained by a subsequent study by Lepori et al (2018), which examined the RG scores of 2,258 European and 4,355 US Higher Education institutions. Institutional RG scores were found to be correlated with the number of publications rather than their quality (Lepori et al, 2018).…”
Section: Metricsmentioning
confidence: 94%
“…Both findings may be explained by a subsequent study by Lepori et al (2018), which examined the RG scores of 2,258 European and 4,355 US Higher Education institutions. Institutional RG scores were found to be correlated with the number of publications rather than their quality (Lepori et al, 2018).…”
Section: Metricsmentioning
confidence: 94%
“…Besides the organizational name (in English and national language), localization information and the website, OrgReg also includes organizational acronyms as experience showed that they are frequently used when referring to the organization. The experience made in matching OrgReg with institutional profiles in ResearchGate (Lepori, Thelwall and Hoorani 2018) showed that this information is sufficient for a precise matching, without having to store in the register name variants, with the exception of (major) changes in the official name.…”
Section: Orgreg As An Interlinking Toolmentioning
confidence: 99%
“…This applies to data derived from administrative sources (Lepori, Bonaccorsi, Daraio, et al 2015), from international databases on publications (Waltman, Calero-Medina, Kosten, et al 2012) and patents (De Rassenfosse, Dernis, Guellec, Picci and de la Potterie, Bruno van Pottelsberghe 2013), therefore overcoming a major limitation of many current studies based solely on output data (Abramo and D'Angelo 2016). Further, the availability of a stable list of public research organizations allows matching with data derived from on-line sources, such as institutional websites and Wikipedia, as well as of social media, such as ResearchGate (Lepori, Thelwall and Hoorani 2018) and Google Scholar, therefore significantly expanding the realm of available information on research organizations.…”
Section: Introductionmentioning
confidence: 99%